Fiscal shocks and real exchange rate dynamics: some evidence for Latin America - Guglielmo Maria Caporale; Davide Ciferri; Alessandro Girardi (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyses the effects of fiscal shocks using a two-country macroeconomic model for output, labour input, government spending and relative prices which provides the orthogonality restrictions for obtaining the structural shocks. Dynamic simulation techniques are then applied, in particular to shed light on the possible effects of fiscal imbalances on the real exchange rate in the case of six Latin American countries. Using quarterly data over the period 1980-2006, we find that in a majority of cases fiscal shocks are the main driving force of real exchange rate fluctuations.
Keywords: C32; E62; O54; 330; fiscal shocks; real exchange rate; Latin American countries; Schock; Finanzsektor; Kaufkraftparität; Volatilität; Zwei-Länder-Modell; Zeitreihenanalyse; Schätzung; Lateinamerika